Study of Lercanidipine Drug Release from Medicine in Combination with Ramipril in vitro and in vivo - A. A. Shadrin; D. Y. Ivkin; E. V. Flisyuk; I. E. Smekhova; G. A. Plisko; A. A. Karpov; E. D. Semivelichenko (Разработка и регистрация лекарственных средств)
Introduction. Hypertension is the most common non-infectious disease in the world. New clinical recommendations for the diagnosis and management of patients with arterial hypertension are considering the issue of prescribing combination therapy and prefer fixed combinations of drugs in a single pill. The study of the pharmacokinetics of medicinal substances and the consideration of their pharmacokinetic parameters today is a necessary step in the complex of work, both in the creation of new original medicines and in the application of known generic drugs, and this is primarily due to obtaining objective characteristics of all processes occur in the body of the animal (human) with the drug. Pharmacokinetics is assessed in individual studies or as part of efficacy, safety, and tolerability studies.Aim. The study of the release of lercanidipine from bilayer tablets containing two API (ramipril and lercanidipine) in the dissolution medium used for quality control in vitro and release in vivo, after oral administration of the drug to rabbits.Materials and methods. Studies have been conducted on the release of lercanidipine from the combined drug in vitro and in vivo. As a test system were used laboratory rabbits Soviet chinchilla breed. Pharmacokinetic parameters were determined.Results and discussion. A graph of the release of lercanidipine from the combined drug was constructed and the dependence of the concentration of this substance in the blood plasma of rabbits on time was revealed. Calculated pharmacokinetic parameters. An in vivo release study shows that the pharmacokinetics of lercanidipine are consistent with literature data.Conclusion. The test drug has all the advantages of a rational fixed combination of antihypertensive drugs and simplifies therapy, meets the requirements of the latest clinical guidelines.